2022
DOI: 10.7150/ijbs.71520
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of ZEB1 facilitated mesenchymal pancreatic cancer cell ferroptosis

Abstract: Background: Mesenchymal cancer cells, resistant to the traditional regulated cell death, are exquisitely vulnerable to ferroptosis. However, the underlying mechanism has been rarely studied. While glycolipid metabolism rewiring is a critical determination of both cancer cell mesenchymal phenotype and cell death resistance, we are interested in the underlying cross talk between glycolipid metabolism and mesenchymal cancer cell ferroptosis sensitivity. Methods: CCK-8, western blot and clone forming assay were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…[ 69 ] O‐GlcNAcylation of ZEB1 also promotes the transcriptional activity of adipogenesis‐related genes FASN and FADS2, leading to increased synthesis of PUFAs and activating ferroptosis. [ 63 ] O‐GlcNAcylation of the ferritin heavy chain at S179 inhibits its interaction with NCOA4, the ferritinophagy receptor, thereby preventing cells from ferroptosis. [ 29 ] In the present study, we found that ectopic expression of SLC7A11‐S26A mutant could not recover the cystine uptake in SLC7A11‐KO cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 69 ] O‐GlcNAcylation of ZEB1 also promotes the transcriptional activity of adipogenesis‐related genes FASN and FADS2, leading to increased synthesis of PUFAs and activating ferroptosis. [ 63 ] O‐GlcNAcylation of the ferritin heavy chain at S179 inhibits its interaction with NCOA4, the ferritinophagy receptor, thereby preventing cells from ferroptosis. [ 29 ] In the present study, we found that ectopic expression of SLC7A11‐S26A mutant could not recover the cystine uptake in SLC7A11‐KO cells.…”
Section: Discussionmentioning
confidence: 99%
“…The O‐GlcNAcylation of ZEB1 at Ser555 site enhances its stabilization and nuclear translocation and induces lipogenesis‐associated gene transcription activity, which ultimately results in lipid peroxidation‐dependent mesenchymal pancreatic cancer cell ferroptosis. [ 63 ] However, the O‐GlcNAcylation of SLC7A11 has not been investigated yet. Our present study reveals a previously unrecognized post‐translational modification of SLC7A11 in HCC, which was mainly regulated by USP8‐OGT axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found in mesenchymal pancreatic cancer cells that FASN and fatty acid desaturase‐2 (FADS2) expression are connected to the O ‐GlcNAcylation status of the transcription factor zinc finger E‐box‐binding homeobox‐1 (ZEB‐1) at Ser555 67 . The authors highlighted a mechanism by which glucose contributes to mesenchymal pancreatic cancer cells ferroptosis through an O ‐GlcNAcylation‐FASN‐FADS2 axis.…”
Section: O‐glcnacylation and Lipid Biogenesismentioning
confidence: 99%
“…Ferroptosis is controlled by a variety of cellular metabolic pathways, including amino acid metabolism, redox homeostasis, and mitochondrial activity [ 9 ]. In parallel to the metabolism of lipids and amino acids, the effect of glucose, a key fuel source for energy metabolism, also needs to be investigated in the ferroptosis process of cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%